Study Of The Effectiveness Of Flood Control Concepts In The Molibagu River, South Bolaang Mongondow Regency - Tawalujan, Kevin Filindo; Mananoma, Tiny; Swingly Frans Sumarauw, Jeffry (Publikasi Indonesia, 2025)
In 2020, flooding occurred in the village of Molibagu, causing damage and losses for the residents who live and work around the Molibagu River. One of the causes of this flood was heavy rainfall, which triggered an increase in the flow discharge of the Molibagu River. Therefore, an analysis of the flood discharge and water level in the Molibagu River is needed to minimize the potential risk of flooding and to determine effective control strategies based on developed scenarios. The objective of this research was to identify effective scenarios from several alternatives, including normalization and the addition of embankments on the left and right sides of the river, to control flooding. The Molibagu Watershed has an area of 38.7 km². Secondary data in the form of rainfall data was obtained from the Sulawesi I River Basin Office (BWSS-I). The rainfall stations ARR-MRG Kosinggolan Matayangan and MRG Bolangaso Molibagu are the sources of maximum daily rainfall data, which will be analyzed over the period from 2008 to 2022. To obtain the parameters needed to determine the peak discharge of 17.5 m³/s, the HEC-HMS software is used. After obtaining the calibrated parameters, the analysis will continue to determine the design flood discharge for various return periods using the HEC-HMS software. The design flood discharge for the return periods will then be input into the HEC-RAS software to obtain the inundation area and water surface elevation of the Molibagu River. As a form of flood control, three flood control scenarios are applied: normalization, embankments, and a combination of normalization and embankments, using RAS Mapper to model and show the extent of the inundated areas. Based on the simulation results obtained, the second scenario, which involves handling with normalization at the same elevation and based on existing flood discharge, is more effective in reducing water level height and mitigating flood overflow better than handling with levees. However, in this scenario, the river cross-section is not able to reduce the flood discharge at the 50 and 100 year return periods, so a combination of the first and second scenarios is needed to reduce the flood and there is no more inundation.